Toxoplasmic encephalitis IRIS in HIV-infected patients: a case series and review of the literature. Issue 6 (26th July 2010) - Martin-Blondel, Guillaume; Alvarez, Muriel; Delobel, Pierre; Uro-Coste, Emmanuelle; Cuzin, Lise; Cuvinciuc, Victor; Fillaux, Judith; Massip, Patrice; Marchou, Bruno
Abstract : Background: Toxoplasmic encephalitis associated with immune reconstitution inflammatory syndrome (TE-IRIS) is rarely described. Methods: To identify TE-IRIS cases, the authors performed a retrospective study of all HIV-infected patients diagnosed as having TE in our unit between January 2000 and June 2009, and a review of published cases. Results: Three patients out of 65 toxoplasmic encephalitis (TE) cases, together with six from the literature, fulfilled the unmasking TE-IRIS definition. None fulfilled the paradoxical TE-IRIS definition. TE occurred within a median time of 48.5 days (IQ25–75 21–56) after starting antiretroviral therapy. Cases did not have distinctive clinical or neuroimaging features from TE occurring without immune reconstitution. However: (1) cases occurred at a median CD4 lymphocytes count of 222/μl (IQ25–75 160–280); (2) TE occurred in five patients who were supposed to take an effective chemoprophylaxis; (3) two patients had a brain biopsy showing an intense angiocentric inflammatory infiltrating with predominantly CD8 lymphocytes; (4) in one patient, the abnormal length of evolution under treatment might be due to the heightened immune response. Conclusion: Although rare, unmasking TE-IRIS exists and might occur despite effective prophylaxis and an unusually high CD4 lymphocyte count. Immune reconstitution inflammatory syndrome does not modify TE diagnosis and treatment but might extend its clinical course.